Fungicides, seed dresser adjuvants and storage time in the control of Drechslera teres in barley seeds - Reis,Erlei Melo (2012)
In experiments conducted in laboratory, the effect of fungicides, seed dresser adjuvants and storage time in the control of Drechslera teres in seeds of barley cultivar BRS Elis, with 58% incidence, was quantified. Fungicides indicated by barley research (carboxin + thiram, difenoconazole and triadimenol) compared with the mixture carbendazim + iprodione were tested. As seed dresser adjuvants, water (500m mL/100 Kg) and a polymer (150 mL/100 Kg) were used. Treated seeds were stored in paper bags and kept in the refrigerator at 5ºC. At 30-day intervals during six months, seeds were plated on semi-selective Reis's medium (1983). The best control was obtained by the mixtures carboxin + thiram and carbendazim + iprodione and the polymer as seed dresser. The control efficiency was improved by the storage time without negatively affecting seed germination. Due to the transmission efficiency, the fungus eradication in seeds should be pursued.